Ferritin as a Risk Factor for Glucose Intolerance amongst Men and Women Originating from the Indian Subcontinent - Elizabeth A. Hughes; Jeetesh V. Patel; Zosia Bredow; Paramjit S. Gill; Julia Chackathayil; Elif S. Agaoglu; Paul Flinders; Rebecca Mirrielees (International Journal of Endocrinology)
Background. Serum ferritin predicts the onset of diabetes; however, this relationship is not clear amongst South Asians, a population susceptible to glucose intolerance and anaemia. Objective. This study tests whether ferritin levels reflect glucose tolerance in South Asians, independent of lifestyle exposures associated with Indian or British residence. Methods. We randomly sampled 227 Gujaratis in Britain (49.8 (14.4) years, 50% men) and 277 contemporaries living in Gujarati villages (47.6 (11.8) years, 41% men). Both groups underwent a 75 g oral-glucose-tolerance test. We evaluated lifestyle parameters with standardised questionnaires and conducted comprehensive clinical and lab measurements. Results. Across sites, the age-adjusted prevalence of diabetes was 9.8%. Serum ferritin was higher amongst diabetics (P=0.005), irrespective of site, gender, and central obesity (P≤0.02), and was associated with fasting and postchallenge glucose, anthropometry, blood pressure, triglycerides, and nonesterified fatty acids (P<0.001). Diabetes was less in those with low ferritin (<20 mg/mL), P<0.008, and risk estimate = 0.35 (95% CI 0.15–0.81), as were blood pressure and metabolic risk factors. On multivariate analysis, diabetes was independently associated with ferritin (P=0.001) and age (P<0.001). Conclusion. Ferritin levels are positively associated with glucose intolerance in our test groups, independent of gender and Indian or UK lifestyle factors.